2015
DOI: 10.1021/acschemneuro.5b00165
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Molecular Chaperones Improves Mitochondrial Bioenergetics and Decreases the Inflammatory Transcriptome in Diabetic Sensory Neurons

Abstract: We have previously demonstrated that modulating molecular chaperones with KU-32, a novobiocin derivative, ameliorates physiologic and bioenergetic deficits of diabetic peripheral neuropathy (DPN). Replacing the coumarin core of KU-32 with a meta-fluorinated biphenyl ring system created KU-596, a novobiocin analogue (novologue) that showed neuroprotective activity in a cell-based assay. The current study sought to determine whether KU-596 offers similar therapeutic potential for treating DPN. Administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 67 publications
(138 reference statements)
4
87
0
Order By: Relevance
“…Macrophage infiltration and proliferation have been observed in nerves from mouse models of diabetes 97,98 , and upregulation of proinflammatory genes during activation of inflammatory pathways in the PNS [99][100][101] further implicates involvement of RAGE-mediated Schwann cell involvement in the inflammatory response. One up regulated gene encodes the S100 calcium binding protein A8/A9 (REF.…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 95%
“…Macrophage infiltration and proliferation have been observed in nerves from mouse models of diabetes 97,98 , and upregulation of proinflammatory genes during activation of inflammatory pathways in the PNS [99][100][101] further implicates involvement of RAGE-mediated Schwann cell involvement in the inflammatory response. One up regulated gene encodes the S100 calcium binding protein A8/A9 (REF.…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 95%
“…Recent work from our lab has shown that Hsp70 may play a role in affecting the expression of TXNIP. RNA-seq analysis of mRNA from DRG of Type 1 diabetic mice showed a 2-fold elevated expression of TXNIP expression (Ma et al, 2015) and treating diabetic mice with the chaperone modulator, KU-596 (see section 5.0), suppressed TXNIP expression to control levels (Fig. 1A).…”
Section: 0– Intracellular Hsp70mentioning
confidence: 99%
“…Importantly, the efficacy of modulating chaperones is not limited to neurodegenerative diseases driven by the formation of protein aggregates. Hsp70 has also been shown to downregulate inflammatory signaling, decrease oxidative stress and improve mitochondrial function in DPN and other conditions whose etiology is not linked to the formation of protein aggregates (Ianaro et al, 2003; Jones et al, 2011; Li et al, 2012; Ma et al, 2015; Madden et al, 2008; Saibil, 2013; Zhang et al, 2012). However, an important aspect of Hsp70 biology that must be considered in moving forward in therapy development is how modulating the intra- versus extracellular pools of Hsp70 may affect disease progression.…”
Section: 0– Molecular Chaperonesmentioning
confidence: 99%
See 2 more Smart Citations